Infant development the essential readings (Essential Readings in Developmental Psychology, 2000)
"Infant Development: The Essential Readings introduces the reader to the field of infancy research and to some of the current, lively controversies within the area." "Each of the articles within the reader has been chosen to reflect the dynamic, changing nature of the subject and the diversity of research and thinking within the area of infant development. The articles have also been selected to be accessible to students at all levels. These articles are all by leading infancy researchers, and they are introduced and contextualized by the editors. Suggestions for further reading are made to give students an ideal starting point for exploration of the key topics in infant development."--BOOK JACKET.